Simultaneous Opposition Tendon Transfer with Median Nerve Decompression for Severe Bilateral Carpal Tunnel Syndrome in Adolescents with Hunter Syndrome: A Case Report. Issue 11 (November 2020) - Uemura, Takuya; Okada, Mitsuhiro; Terai, Hidetomi; Yokoi, Takuya; Onode, Ema; Shintani, Kosuke; Konishi, Sadahiko; Nakamura, Hiroaki
Abstract : Summary: Although carpal tunnel syndrome (CTS) is exceedingly rare in children, its prevalence in those with Hunter syndrome, mucopolysaccharidosis type II, is high. With the advent of hematopoietic stem cell transplantation and enzyme replacement therapy, the survival of patients with Hunter syndrome has dramatically improved. With improved longevity in these patients, CTS continues to progress with age. However, most patients with Hunter syndrome with CTS have generally been treated with an open carpal tunnel release (OCTR) only, without considering the severity. Here, we present a mid-term follow-up of a 16-year-old patient with Hunter syndrome associated with severe bilateral CTS successfully treated by the simultaneous opposition tendon transfer with an OCTR to improve the thumb function. Intraoperatively, the median nerve was constricted and flattened with congestion by the transverse carpal ligament. External and internal neurolysis of the scarred median nerve were performed and found epineural fibrosis and tethered epineurium. An intraneural lipoma of the left median nerve was especially resected with epineurotomy. During neurolysis and tendon transfer, the soft tissue was very viscous, a characteristic of mucopolysaccharidoses. Transferring the tension of the palmaris longus tendon to the abductor pollicis brevis for the thumb palmar abduction should be stronger than routine adult patients because the soft tissue such as the tendon excursion is stickier and more contracted in patients with Hunter syndrome. Postoperatively, a thumb spica splint was applied for 3 weeks, and then active motion exercises were cautiously started to prevent joint contracture. Early recognition and surgical intervention for CTS are essential in patients with Hunter syndrome.